The RENDAHNYA IMPLEMENTASI PEMBELAJARAN BAHASA INGGRIS DALAM SEKOLAH DASAR NEGERI DI CIKARANG: indonesia - Davin, Ardell (Lentera Jurnal Manajemen, 2024)
This study aims to examine the low implementation of English language learning in public elementary schools (SDN) in the Cikarang area. English, as an international language, should ideally be introduced from an early age to strengthen the competitiveness and preparedness of the younger generation in facing the global era. However, field observations reveal several obstacles, such as a lack of competent teachers, limited learning media, insufficient professional training, and the absence of dedicated English teachers in most of the surveyed schools. This research adopts a descriptive qualitative approach through semi-structured interviews with teachers from five public elementary schools in Cikarang. The results indicate that most teachers come from general educational backgrounds and have not received any specialized English training, leading to a lack of confidence in teaching the subject. Nevertheless, the teachers acknowledge the importance of English and demonstrate enthusiasm for improving teaching quality, as do the students, who show a strong interest in learning the language. This study recommends the provision of regular training sessions, the placement of specialized English teachers, and the development of interactive teaching materials and methods to enhance the effectiveness of English language education in elementary schools.